Communication strategy of The Regional Agency for Disaster Management of Sumbawa Regency in disaster mitigation - Anshori, Muhammad Syukron; Hatima, Husnul; Lestari, Ajeng (Manajemen Komunikasi, 2022)
Disaster management is needed to minimize the impact of disasters. It aims to prepare and educate people living in disaster-prone areas to be better prepared to respond to the impact of disasters. Sumbawa Regency is an area prone to natural disasters such as earthquakes, floods, fires, landslides, and others. The Regional Agency for Disaster Management (BPBD) of Sumbawa Regency is to implement a program called "Desa Tangguh Bencana" to improve disaster mitigation management in Sumbawa. This study aims to determine the communication strategy of disaster mitigation planning by BPBD of Sumbawa Regency, early 2020–2021. This study uses descriptive methods and data collection techniques by observation and in-depth interviews with the initiators of the program and their effectiveness in tackling the impact of disasters. The study results showed that communication strategy is the main point of successful program implementation by selecting communicators with scientific credibility, expertise, professionals related to disasters, and good public speaking skills. The targets are the village government and, of course, the people who directly feel the impact of the disaster. A communication platform is used to introduce the program to the community using face-to-face meetings such as outreach and campaigns through social media, using a website network to reach the general public to get information regarding the program's presence. The content of the information submitted in this program is information related to disaster mitigation, stages, and implementation carried out by BPBD in dealing with disasters for people whose living areas are often affected by natural disasters.